Evaluación técnico-financiera del fraccionamiento del gas natural producido en el Piedemonte Llanero de Colombia (2018)
The technical-financial evaluation of the natural gas processing produced in Piedemonte Llanero of Colombia, shows the process of development and evaluation of the conceptual design of a gas fractionation plant with capacity for 120 MMSCFD, delivering quantitative and qualitative results that determine the project viability. In the beginning of the project, the authors proceeded to describe the geological generalities of Floreña and Pauto Fields, writing about the Fields history, its structural geology and its petroleum system. Then they proceeded to talk about the natural gas generalities, and how they describe the characterization of the gas extracted from Floreña and Pauto Fields.